La enseñanza aprendizaje de la lectoescritura en segundo año de Educación Básica - Gallardo Chango, Silvana Nataly (2022)
The research carried out assumes the following scientific problem: How to improve literacy in the teaching-learning process of Language and Literature in the second year of Basic Education? To solve the problem, the general objective is formulated: To improve literacy in the teaching-learning process of Language and Literature through the application of a methodological strategy. The methodology used assumes the mixed approach and the inductive-deductive method, observation, survey, descriptive statistics, the criteria of specialists, the socialization workshop with users and the analysis of the products of the activity are used. With the research process carried out, the following conclusions are reached: The establishment of the epistemological foundations of the teaching-learning of literacy in students of Basic Education allowed a diagnosis of its possible manifestations and the elaboration of a methodological proposal for second-year students. of Educational Unit 14 of October "Vicente Rocafuerte" of the canton Pujili, province of Cotopaxi; The diagnosis made allowed revealing the difficulties of reading and writing in the teaching process and finding alternatives to its solution. The design of the methodological strategy for the teaching-learning of literacy of the second-year students of the Educational Unit October 14 "Vicente Rocafuerte" was feasible and viable based on the criteria of specialists and users and the partial incursion of the methodological strategy in practice and its preliminary results allow us to support that it is a viable and pertinent alternative to the solution of the research problem